Mandarin–Italian Dual-Language Children’s Comprehension of Head-Final and Head-Initial Relative Clauses - Hu, Shenai; Costa, Francesca; Guasti, Maria Teresa (Frontiers in Psychology, 2020)
The acquisition of languages by children using two languages is a matter of debate as many factors contribute to the success of this type of acquisition. We focus on how the competence of dual language children changes in their two languages as a function of length of exposure and establish whether there are reciprocal influences during language development. We examined the comprehension of subject and object relative clauses in a group of 6-year-old (younger) and 8-year-old (older) Mandarin-Italian dual language children. After three years of exposure to Italian, the younger group reached the same level of competence in the comprehension of relative clauses in their two languages, and after five years of exposure to Italian, the older group had a better comprehension of relative clauses in Italian than in Mandarin. Acquiring two languages leads to bidirectional influence, beyond a reciprocal support. Finally, some penalty may be observed in the acquisition of subject head-final RCs, which is not evident in that of subject head-initial RCs.